PERANCANGAN HOTEL RESORT DI WISATA ALAM GUCI TEGAL DENGAN PENDEKATAN ARSITEKTUR TROPIS - Andri Ulumudin; Tri Endangsih; Harfa Iskandaria (MAESTRO, 2021)
Tourism has an important role for the economic growth of a region. One of the tourist destinations that are currently in great demand by tourists when enjoying holidays is nature tourism. There is an area that has natural beauty typical of mountainous areas, namely Guci Nature Tourism. The tourist attraction is located in Guci Village, Bumijawa District, Tegal Regency. However, there are no resort hotel accommodation facilities in the Guci Tegal Tourism Object area to support the completeness of lodging in the Tegal Tourism Object Area. Given the high number of visitors to this tegal urn tour every year and the potential for its natural beauty. Therefore, the purpose of building a resort hotel in this area is to attract more tourists visiting these tourist attractions so that they can make the Guci Tegal Tourism Object better known by local and foreign tourists and provide comfort and safety for visiting tourists..